PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVC SEKOLAH DASAR NEGERI 108 PEKANBARU - Lazim; N, Zulkifli (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2014)
The problem in this research was the low score of students’ learning outcomes in social science. There were still many students who did not understand basic concepts and tended to memorize examples. This condition was shown by only 58.07% of 31 students achieving the Minimum Completeness Criteria (KKM) based on students’ test scores in class IVC of SDN 108 Pekanbaru for the cooperative subject. The students’ average score was 62.4, while the KKM determined by the school was 68. Based on this problem, it was necessary to conduct classroom action research using the cooperative learning model of the Teams Games Tournaments (TGT) type. This research aimed to determine whether the implementation of the cooperative learning model of the Teams Games Tournaments (TGT) type could improve students’ social science learning outcomes in class IVC of SDN 108 Pekanbaru in the 2013/2014 academic year with 31 students. This research was conducted in two cycles. The first cycle consisted of three meetings with one daily test and the first tournament, while the second cycle consisted of three meetings with one daily test and the second tournament. The instruments used to collect data in this research were teacher observation sheets, student observation sheets, and tests. Through the implementation of the cooperative learning model of the Teams Games Tournaments (TGT) type, students’ learning outcomes improved. The percentage of completeness in the basic score was 54.8% with an average score of 62.40, which increased to 77.4% with an average score of 75.6 in cycle I and further increased to 87.1% with an average score of 81.1 in cycle II. The percentage of teacher activity in cycle I was 81.9% and increased to 92.3% in cycle II. Meanwhile, the percentage of students’ activity in cycle I was 75.4% and increased to 92.2% in cycle II. Based on these data, it can be concluded that the implementation of the cooperative learning model of the Teams Games Tournaments (TGT) type can improve students’ learning outcomes in class IVC of SDN 108 Pekanbaru.